2018
DOI: 10.15294/physcomm.v3i1.14921
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenon of Buying and Selling as Bridging Analogy of Learning Work and Energy

Abstract: Effective physics learning can be designed by recognizing students' difficulties in understanding physics concepts. Students build the concept through experience gained from the environment, so that they unconsciously have the concept in accordance with the understood. Students still have difficulty distinguishing work and energy definitions in physics and in everyday life. The concept of work and energy can be understood by students if students have good analogy skills. The Brain Based Learning (BBL) model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
2
0
4
Order By: Relevance
“…Jembatan konsep analogi (bridging concept analogy) menjadi salah satu strategi yang dapat diterapkan dalam pembelajaran fisika [19]. Konsep yang abstrak dan rumit dapat diajarkan melalui analogi sehinga membantu peserta didik dalam memahami konsep fisika dengan baik, selain itu pembelajaran menggunakan analogi dapat melatih siswa untuk berpikir kreatif dan berpikir tingkat tinggi [20], [21].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Jembatan konsep analogi (bridging concept analogy) menjadi salah satu strategi yang dapat diterapkan dalam pembelajaran fisika [19]. Konsep yang abstrak dan rumit dapat diajarkan melalui analogi sehinga membantu peserta didik dalam memahami konsep fisika dengan baik, selain itu pembelajaran menggunakan analogi dapat melatih siswa untuk berpikir kreatif dan berpikir tingkat tinggi [20], [21].…”
Section: Pendahuluanunclassified
“…Melalui metode yang tepat, fisika dapat dipelajari dengan relatif mudah dan menyenangkan bagi peserta didik. Konsep jembatan konsep atau dikenal dengan model Teaching With Analogy (TWA) yang dikembangkan oleh Glyn tahun 1995 [9], [10] berupaya menyajikan perbandingan melalui mapping comcept antara konsep rujukan terhadap konsep target [19].…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…In the concept of mechanics, it was found that the discussion of the matter of work and energy experienced a misunderstanding of the most important concepts. The work and energy theorem derived from Newton's second law is often indistinguishable from the energy equation, so students often use the wrong equation to solve problems (Desianna & Nugroho 2019;Chabay et al 2019). Research on students' understanding of energy materials has received wide attention from both high schools and universities.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review reveals that the concept of work is discussed in conjunction with the concepts of power, force, and energy. These studies are grouped under six headings according to their objectives: (a) explaining the correlation between work and energy (Adamczyk & Willson, 1996;Doménech et al, 2015;Gutlerrez, Zuza, & Gulsasola, 2015;Hartmann & Priemer, 2018); (b) determing incorrect comprehension levels of students about work, power, and energy (Bahar, Öztürk, & Ateş, 2002;Erduran-Avcı, Ünlü, & Yağbasan, 2009); (c) identifying alternative concepts in work, power and energy subjects; (Küçük, Çepni, & Gökdere, 2005;Pastırmacı, 2011), (d) evaluating students' perception levels about energy and related concepts (Duit, 1984;Goldring & Osborne 1994;Hırça, 2008;Küçük, Çepni, & Gökdere, 2005;Trumper, 1998;Ünal-Çoban, Aktamış, & Ergin, 2007;Watts, 1983), (e) eliminating alternative conceptions about work and energy (İpek Akbulut, Şahin, & Çepni, 2013); and (f) applying new approaches in teaching work, power and energy subjects; (Büyükdede & Tanel, 2018;Cerit Berber, 2008;Cerit Berber & Sarı, 2009;Desianna, Nugroho, & Ellianawati, 2019;Ergin, 2011;Mustofa & Asmichatin, 2019). There are a limited number of studies focusing specifically on work, for example, misconceptions about the concept (Erduran Avcı, Kara, & Karaca, 2012) or prospective teachers' skills of distinguishing the difference between negative-positive work (Uzunkavak, 2009).…”
Section: Introductionmentioning
confidence: 99%